Film production management how to budget, organize, and successfully shoot your film - Cleve, Bastian (Routledge, 2018)
This new and updated fourth edition of Film Production Management provides a step-by-step guide on how to budget, organize, and successfully shoot a film and get it onto the big screen. Whether you are a film student or film production professional just getting started in the industry, this book is an indispensable resource for day-to-day business on the set.